Research Gaps and Challenges in the Conservation and Use of North American Wild Lettuce Germplasm - Lebeda, Aleš; Křístková, Eva; Kitner, Miloslav; Majeský, Ľuboš; Doležalová, Ivana; Khoury, Colin K.; Widrlechner, Mark P.; Hu, Jinguo; Carver, Daniel; Achicanoy Estrella, Harold Armando; Sosa, Chrystian C. (Wiley, 2019)
The North American crop wild relatives (CWR) of lettuce (Lactuca L.) represent an underexplored pool of genetic diversity of potential value to breeding programs. The 10 species belong to three different groups: a native clade including at least six allotetraploid species [L. biennis (Moench) Fernald, L. canadensis L., L. floridana (L.) Gaertn., L. graminifolia Michx., L. hirsuta Muhl. ex Nutt., and L. ludoviciana (Nutt.) Riddell], a diploid clade with one species [L. tatarica (L.) C. A. Mey. subsp. pulchella (Pursh) Stebbins], and a clade related to the cultivated taxon (L. sativa L.) with three non-native species (L. saligna L., L. serriola L., and L. virosa L.). In this review, we examine the role of herbarium and genebank holdings in taxonomic and other foundational studies, as well as for germplasm exploration and use. We compile the state of knowledge on the ranges of lettuce CWR in North America, modeling the potential distributions of the species and assessing their ex situ and (for native species) in situ conservation status. We categorize seven of the species as high priority for further conservation and three as medium priority, with none currently considered low priority or sufficiently conserved. Further, we review morphological, phenological, genetic diversity, and pest and disease information with regard to North American species. We conclude by outlining the critical gaps and describing a way forward for addressing challenges in the conservation and use of North American wild lettuce germplasm.